2017
DOI: 10.1002/wps.20442
|View full text |Cite
|
Sign up to set email alerts
|

The third wave of cognitive behavioral therapy and the rise of process‐based care

Abstract: The third wave of cognitive behavioral therapy and the rise of processbased careThe term cognitive behavioral therapy (CBT) identifies a family of interventions that are widely recognized as the set of psychological treatments with the most extensive empirical support 1 . CBT is not monolithic, however, and it has been through several distinct eras, generations, or waves. The first generation of this tradition was behavior therapy: the application of learning principles to well-evaluated methods designed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
295
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 462 publications
(320 citation statements)
references
References 11 publications
9
295
0
16
Order By: Relevance
“…Results suggest that strategies and procedures such as resting, exercise, and activity pacing are collectively not as influential as the development of processes such as self‐efficacy and aspects of PF for individuals with fibromyalgia. This finding is consistent with previous studies that have used the BPCI‐2 in chronic pain samples (McCracken & Vowles, ; Vowles & McCracken, ; Vowles, McCracken, et al, ; Vowles, Sowden, et al, ), and is also consistent with trends in clinical psychology toward process‐based CBT (Hayes & Hofmann, ). There is some evidence to suggest that processes such as self‐efficacy and indeed pain acceptance are change mechanisms within treatment for chronic pain, regardless of the treatment approach (Åkerblom, Perrin, Fischer, & McCracken, ).…”
Section: Discussionsupporting
confidence: 91%
“…Results suggest that strategies and procedures such as resting, exercise, and activity pacing are collectively not as influential as the development of processes such as self‐efficacy and aspects of PF for individuals with fibromyalgia. This finding is consistent with previous studies that have used the BPCI‐2 in chronic pain samples (McCracken & Vowles, ; Vowles & McCracken, ; Vowles, McCracken, et al, ; Vowles, Sowden, et al, ), and is also consistent with trends in clinical psychology toward process‐based CBT (Hayes & Hofmann, ). There is some evidence to suggest that processes such as self‐efficacy and indeed pain acceptance are change mechanisms within treatment for chronic pain, regardless of the treatment approach (Åkerblom, Perrin, Fischer, & McCracken, ).…”
Section: Discussionsupporting
confidence: 91%
“…There is growing evidence for CBT skills demonstrating significant therapeutic gains; such as case formulation‐driven strategies to repair alliance ruptures, enhanced engagement through homework, and Socratic dialogue (Falkenström, Ekeblad, & Holmqvist, ; Kazantzis et al, ; Kazantzis, Brownfield, Mosely, Usatoff, & Flighty, ; Kazantzis, Luong, et al, ). This finding reflects the potential for maximisation in CBT competency training programs that is consistent with the emerging evidence linking process‐based CBT as a core clinical competency (Hayes & Hofmann, , ; Hofmann & Hayes, ).…”
Section: Discussionsupporting
confidence: 84%
“…The Association for Behavioural and Cognitive Therapies in the United States reported implications of their doctoral level guidelines for education and training in CBT, recommending a progression towards a scientific and ethical philosophy in CBT training programs to maximise CBT efficacy (Klepac et al, ). This work highlighted the opportunity to focus on processes and mechanisms of CBT, as opposed to specific therapy protocols, that led to flexible process‐driven treatment (e.g., Barlow et al, ; Hayes & Hofmann, , ; Hofmann & Hayes, ). Incorporating the principles and procedures of process‐based CBT into a national CBT competency checklist would optimise the EBP of psychology, in that the theoretically derived competencies of CBT will link testable mechanisms moderating and mediating efficacious outcome, and further tailor treatment methods to the needs of individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Mindfulness and acceptance strategies are consistent with general CBT principles, because they target core processes, such as increased emotional awareness and regulation, cognitive flexibility, and goals-based behaviors. 31,32 This is a topic that is outside the boundaries of this chapter, but that is likely to become part of the future of psychotherapy. As we will discuss throughout this review, mindfulness targets one such core processes that has demonstrated efficacy in reducing anxiety and depression symptom severity, both as the core treatment ingredient, as well as when integrated into other treatments.…”
Section: Introductionmentioning
confidence: 99%